Cultural diplomacy during Kennedy's presidency: home and abroad - Klynina, Tetiana (Ukrainian Cultural Studies, 2024)
Background. The article is devoted to an overview of the general strategy of cultural diplomacy during the presidency of John F. Kennedy (1961–1963), considered one of the important instruments of US foreign policy. In the Cold War conditions, culture became a means of mutual understanding between peoples and a strategic element of political influence and opposition to the communist bloc. The Kennedy administration implemented several initiatives that confirmed the importance of culture in the diplomatic dimension, including adopting the Act on Reciprocal Educational and Cultural Exchange (1961).  The purpose of the study is to analyze the use of culture as a means of diplomacy that served to achieve the foreign policy and strategic goals of the Kennedy administration.Methods. The study is based on the principle of historicism, a systematic approach, problem-chronological and descriptive methods. Content analysis of documents, speeches of President Kennedy and some cultural programs, such as Art in Embassies, was used. Results. The article provides a brief comparative analysis of cultural diplomacy of different periods. The article demonstrates that the cultural diplomacy of the Kennedy administration was systemic and centralized. Although official statements emphasized the independence of cultural initiatives, they were coordinated by Washington, considering the strategic interests of the United States, and not the cultural needs of the regions to which these initiatives were directed. The main components of this strategy were cultural exchanges, exhibitions, international programs, and the involvement of prominent figures in art and science in the promotion of American democratic values. Conclusions. The John F. Kennedy administration demonstrated the use of cultural diplomacy in the context of global confrontation. The efforts of the US government in the field of culture became an important tool of "soft power", aimed not only at improving the international image of the country but also at creating a dialogue with the peoples of other states. At the same time, the centralization of such initiatives has aroused criticism due to insufficient attention to the cultural needs of individual regions.
Keywords: cultural diplomacy; J. Kennedy; Cold War; arts; educational and cultural exchanges